Investigation of wettability properties of laser surface modified rare earth Mg alloy - Khadka, Indira (2018)
Mg and its alloys are used in various application areas, where the wetting property is a special requirement. For example, surface wettability of a biomaterial plays a vital role in cell adhesion and proliferation. In this context, rare earth Mg alloy (WE54), a potential biomaterial, was studied to examine its wetting behavior. In order to tailor the surface properties, laser surface melting (LSM), a single process method, was adopted. In this paper, the effective change on wettability properties of WE54 after LSM process was studied under deionized water and simulated body fluid. A 500 watt nanosecond pulse Nd:YAG laser having a wavelength of 1064 nm was used to modify surface properties. Microstructure and surface morphology were examined by scanning electron microscope and profilometer, respectively. Cellular structure and some buds were observed on the laser melted surface of WE54. Evaporation of Mg and enrichment of Y up to 12.10% and 13.43% were observed. The contact angle was reduced from 81o to 41.03o in deionized water after laser treatment, whereas in SBF solution it was reduced to 23.13o. It indicates that WE54 alloy also has a bio-wettability characteristic, which is very important for bio-applications.